ISSUES OF LEGAL CERTAINTY AFTER THE ISSUANCE OF MINISTER OF MANPOWER REGULATION NO. 18 OF 2022 ON MINIMUM WAGE DETERMINATION FOR 2023. - Armantjoneng; S.Sewu , Lindawaty; Septina Basani, Christin (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
In November 2022, the government issued Minister of Manpower Regulation No. 18 of 2022 concerning the Determination of Minimum Wage for 2023, despite already having regulations related to wages, namely Government Regulation No. 36 of 2021 concerning Wages.  The emergence of this regulation is considered to cause legal uncertainty as there is already a government regulation on wages and it undermines the results of the constitutional review of the Job Creation Law, where the Constitutional Court's decision states that the Job Creation Law remains valid for the next 2 years and does not require additional regulations. This has led to legal uncertainty regarding wage regulations. The research method employed in this study is the normative legal research method, which involves examining literature or secondary data.  The approach used included the statute approach, which analyzes all legislation and regulations related to the legal issues being addressed, and the conceptual approach, which stems from perspectives and doctrines within legal studies. The data used consisted of secondary data obtained through literature reviews and primary data obtained through interviews with respondents and relevant institutions. The results of this research are expected to provide answers to the dualism in legislation regarding wages, particularly for legal certainty for employers, workers, and investors. The determination of minimum wage is indeed crucial in the economic field, as it relates not only to the purchasing power of the society for wage increases but also to legal certainty needed by employers and investors, including the government's consistency in enacting legislation.